Estimating the Effects of Nonpharmaceutical Interventions of COVID-19 in Sudurpaschim Province, Nepal - Chanda, Nar Bahadur; Adhikari, Khagendra; Gautam, Ramesh; Pokharel, Anjana; Uprety, Kedar Nath (Journal of Institute of Science and Technology, 2023)
Due to ongoing viral evolution and frequent outbreaks, responding to the pandemic has been challenging for countries with limited resources, like Nepal. In this study, we retrospectively estimated the impact of nonpharmaceutical interventions (NPIs) in Sudurpashchim province of Nepal using COVID-19 second wave data (20 March-31 August 2021) by using the mathematical model. We estimated extremely low (2%) detection of new cases in Sudurpashchim, and only 10% border screening with Antigen tests among the returnees in Sudurpashchim from India during the Delta surge which was not sufficient to lower the burden of the pandemic. The lockdown implemented during the pandemic was successful in lowering the disease burden. The control interventions were effective which reduced the 34% of new cases and 28% of active cases during the peak time and overall cases by 12.3% from 20 March-31 August 2021. During the peak of the pandemic, control intervention reduced the number of patients in regular beds by 27%, ICU by 31%, and ventilators admissions each by 33%. Our results explore that, without sufficient detection of new cases in the community, border screening alone is not sufficient for the diseases control. Therefore, in the absence of pharmaceutical interventions, it is important to combine social distance with adequate case detection, which is made even more effective by perfect border screening, to reduce the burden of the pandemic.